A bag of marbles [videorecording (DVD)] - Duguay, Christian; Duguay, Christian; Le Clech, Dorian; Palmieri, Batyste Fleurial; Bruel, Patrick; Joffo, Joseph (Passion River, 2018)
Two young Jewish brothers escape the Nazis in occupied France.